DETERMINATION OF WORK INDEX OF GRAPHITE FROM SAMAN-BURKONO (NIGERIA) USING MODIFIED BOND'S METHOD (Nigerian Journal of Technology, 2019)
This report covers the work index determination of Saman-Burkono graphite. The test sample was obtained from Saman-Burkono in Ningi Local Government Area of Bauchi state, while reference material (coal) was sourced from Okaba coal mine, Ankpa Local Government Area of Kogi State. A known weight of graphite sample and coal were crushed, pulverized and ground using the laboratory milling machine. The two samples were grinded with two cells of diameter 3.5cm and 222g weight. The analysis of the feed  size fort the two samples was found graphically to be 180?m and 175?m, and ball mill discharge was 130?m and 140?m respectively. The  work index of  a coal as reference material was 7.65 kWh/ short ton, this was used to calculate the work index of the graphite which was found to be 11.047 kWh/short ton, being the required energy to comminute one ton of graphite. http://dx.doi.org/10.4314/njt.v38i3.10